2016
DOI: 10.1002/macp.201500523
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dual‐Cure Initiating System for Cationic Polymerization of Epoxides

Abstract: Pyrylium salts are found to be effective initiators for both photochemical and thermal cationic polymerization of epoxy resin. The photopolymerization results show that triphenylpyrylium salt derivatives are the most efficient structures. These compounds also exhibit some thermal reactivity at room temperature in the absence of light. However in such case, the gel time of the resin is quite high. Therefore, to speed up the thermal reaction, nucleophilic compounds are added as coinitiators, these compounds bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…TPP + has been shown to exhibit some reactivity with respect to the polymerization initiation of epoxides through both thermal and photochemical processes . Regarding the thermal reaction at room temperature, it is strongly accelerated when isobutylvinylether 3 is used as a coinitiator, although the mechanism is still unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TPP + has been shown to exhibit some reactivity with respect to the polymerization initiation of epoxides through both thermal and photochemical processes . Regarding the thermal reaction at room temperature, it is strongly accelerated when isobutylvinylether 3 is used as a coinitiator, although the mechanism is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Originally used to photochemically cure thin layers of epoxides, these onium salts have been recently used for thick material curing . Indeed, among the recent works devoted to dual‐cure initiating systems, some efforts have been especially focused on epoxide curing by photoinduced thermal frontal polymerization . The majority of these works are based on the decomposition of a photoacid generator under irradiation and a thermal redox reaction mediated via radicals in depth, where the light does not penetrate anymore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that different frontal polymerization reactions can be used to cure the whole thickness of a composite, a process that takes advantage of a surface irradiation of the sample for initiating the reaction over the whole thickness. 3 These reactions have been developed for both unsaturated polyester [4][5][6] and epoxy [7][8][9][10][11][12][13][14] resins. Recently, it has been found that 2,4,6-triphenylpyrylium salt can act as both photo-and thermal-initiator, leading to unprecedented efficiency in the photoinduced thermal frontal polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a trend to substitute the thermal resin by a photoreactive resin, taking the advantage of the photopolymerization process . Indeed, photopolymerization is a reaction, which is fast, solvent free, and offers excellent space and time control . Consequently, it could provide an efficient alternative to the use of thermally prepared prepregs.…”
Section: Introductionmentioning
confidence: 99%